PENGEMBANGAN SISWA MELALUI PEMBELAJARAN MENULIS DI SEKOLAH DASAR - K. Endang Sri Nuryani (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2016)
One aspect that was developed in the implementation of the curriculum in primary schools in 2013 is the aspect of "creativity". This aspect is developed through the activity of observing, questioning, reasoning, and try;. This aspect is taught through a "thematic". The development of this aspect can be done through a variety of learning activities in schools. One of them is through learning to write. Writing activities are believed to be used to develop the creativity of students. Because in the proc ess of writing, the author of processing what they see, they read, they listen, and they feel to be the text that is meaningful and interesting. And through the writing process, students develop other competencies as well, such as grammatical competence, textual, and sociocultural. Thus, through creative writing students will develop.Keywords: child creativity, study write, elementary school.